1990
DOI: 10.1139/t90-095
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of toppling

Abstract: Evidence of large-scale toppling deformation has been reported in association with deep-seated landslides affecting mountain slopes along the Beaver River valley, Glacier National Park, British Columbia, Canada. A study has been undertaken to quantitatively investigate the relationship between the toppling mass movement process and the deep-seated landslides; specifically, whether the landslides represent a limiting condition of the toppling process. This is the first of two papers that describe the study. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 0 publications
0
36
0
2
Order By: Relevance
“…The equations to reach other geometric parameters including a1, a2, b and yn can be addressed in Appendix A. It is shown that the interface between deformation blocks and the base is stepped, and its overall dip ψb can be valued in the range shown in Equation (1) [8,14,23]. It is shown that the interface between deformation blocks and the base is stepped, and its overall dip ψ b can be valued in the range shown in Equation (1) [8,14,23].…”
Section: Mechanical Model and Analytical Solution To Toppling Slope Fmentioning
confidence: 99%
“…The equations to reach other geometric parameters including a1, a2, b and yn can be addressed in Appendix A. It is shown that the interface between deformation blocks and the base is stepped, and its overall dip ψb can be valued in the range shown in Equation (1) [8,14,23]. It is shown that the interface between deformation blocks and the base is stepped, and its overall dip ψ b can be valued in the range shown in Equation (1) [8,14,23].…”
Section: Mechanical Model and Analytical Solution To Toppling Slope Fmentioning
confidence: 99%
“…It is a mass movement of rock on a slope characterized by downslope overturning, which can involves flexure, rotation and interaction of rock blocks (Pritchard and Savigny, 1990;Alejano et al, 2010). Toppling has been commonly classified into four principal types: block toppling, flexural toppling, blockflexural toppling, and secondary toppling (Goodman and Bray, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The toppling process can be triggered by natural factors (rainfalls, earthquakes, etc.) (Hack et al, 2007) as well as human engineering activities (Pritchard and Savigny, 1990;Tu et al, 2007;Huang et al, 2013), and it can pose a serious hazard.…”
Section: Introductionmentioning
confidence: 99%
“…Discontinuum-based methods such as distinct element code (UDEC) and discontinuous deformation analysis (DDA), by contrast, have achieved great success in accounting for the kinematics of discrete blocks and have been widely used to investigate the toppling failure mechanisms of rock slope [7][8][9][10][11][12][13][14]. However, all the analyzed rock masses are assumed to be divided by fully-persistent joints, fracturing through intact rock-bridge is not taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…In order to accurately predict rock slope failure, including both fracturing through intact rock mass and kinematic behavior of a failed rock slope, a lot of methods have been developed. Pritchard and Savigny [7] used UDEC to model the failure mechanism of flexural toppling. A linear elastic-plastic constitutive relationship was assigned to blocks, when the strength of the block material was reached, slope fracture failure occurred.…”
Section: Introductionmentioning
confidence: 99%